Physical drivers of bio-optical properties in the Guangdong-Hong Kong-Macao Greater Bay Area during the winter dry season - Xu, Wenlong; Hu, Shuibo; Hayward, Alex; Wang, Zuomin; Liu, Shuaiwei (Frontiers in Marine Science, 2025)
Understanding the variability of bio-optical properties in coastal seas is essential to assessing the impact of natural and anthropogenic activities on the quality of the coastal environments and their resources. This study investigated the vertical distribution of bio-optical properties and their potential driving forces in the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) using a bio-optical dataset collected during the winter dry season. The hydrographic and biogeochemical properties observed across the GBA exhibited significant spatial variability, allowing the classification of the waters into three distinct regions: estuarine diluted water (EDW), Guangdong coastal current water (GCCW), and dense shelf water (DSW). Our findings show that EDW exhibited beam attenuation and optical backscatter coefficients an order of magnitude greater compared to the other two regions, which was attributed to factors such as higher concentrations of suspended particulate matter and organic material from estuarine sources. In contrast, the GCCW was characterized by lower salinity, temperature, and suspended particulate matter and displayed reduced turbidity near the coast, whereas nutrient-rich GCCW waters transported to the mid-shelf region supported increased phytoplankton biomass and a greater abundance of micro-phytoplankton. By exploring the bio-optical characteristics and their underlying processes in the GBA, this study enhances our understanding of the complex dynamics shaping the optical properties of coastal waters in this heavily urbanized region.